Case Report Diabetic Ketoacidosis during Pregnancy - Mohammad Saleh Khaskheli, Abdul Aziz Sahto, Waseem Raja, Aijaz Awan, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2012)
Diabetic Ketoacidosis is life is a life threatening complication of diabetes, characterized by hyperglycemia, ketoacidosis and ketonemia. We present a case of 28 year old female with 4-month pregnancy admitted in ICU with vomiting for 2 weeks, fever and breathlessness for 2 days and irritability and abdominal pain for I day. Random blood sugar was 428 mg/d1 and urine ketones 3+. There was no previous history of Diabetes. She was diagnosed as a case of diabetic ketoacidosis.